Modification of a Putative Third Sodium Site in the Glycine Transporter GlyT2 Influences the Chloride Dependence of Substrate Transport - Benito-Muñoz, Cristina; Perona, Almudena; Abia, David; dos Santos, Helena G.; Núñez, Enrique; Aragón, Carmen; López-Corcuera, Beatriz (Frontiers in Molecular Neuroscience, 2018)
Neurotransmitter removal from glycine-mediated synapses relies on two sodium-driven high-affinity plasma membrane glycine transporters (GlyTs) that control neurotransmitter availability. Mostly glial GlyT1 is the main regulator of glycine synaptic levels, whereas neuronal GlyT2 promotes the recycling of synaptic glycine and supplies neurotransmitter for presynaptic vesicle refilling. The GlyTs differ in sodium:glycine symport stoichiometry, showing GlyT1 a 2:1 and GlyT2 a 3:1 sodium:glycine coupling. Sodium binds to the GlyTs at two conserved Na+ sites: Na1 and Na2. The location of GlyT2 Na3 site remains unknown, although Glu650 has been involved in the coordination. Here we have used comparative molecular dynamics simulations of a GlyT2 model constructed by homology to the crystalized dopamine transporter from Drosophila melanogaster by placing the Na3 ion at two different locations. By combination of in silico and experimental data obtained by biochemical and electrophysiological analysis of GlyTs mutants, we provide evidences proving the GlyT2 third sodium ion is held by Glu-250 and Glu-650, within a region with robust allosteric properties involved in cation-specific sensitivity. Substitution of Glu650 in GlyT2 by the corresponding methionine in GlyT1 reduced the charge-to-flux ratio to the level of GlyT1 without altering transport coupling. Chloride dependence of glycine transport was almost abolished in this GlyT2 mutant but simultaneous substitution of Glu250 and Glu650 by neutral amino acids rescued chloride sensitivity, suggesting that protonation/deprotonation of Glu250 substitutes chloride function. The differential behavior of equivalent GlyT1 mutations sustains a GlyT2-specific allosteric coupling between the Na3 site and the chloride site.